Lipase-catalyzed protection of the hydroxy groups of the nucleosides inosine and 2 '-deoxyinosine : a new chemoenzymatic synthesis of the antiviral drug 2 ',3 '-dideoxyinosine - P. Ciuffreda; S. Casati; E. Santaniello (Bioorganic & Medicinal Chemistry Letters, 1999)
The selective acylation of the hydroxy groups of the nucleosides inosine la and 2'-deoxyinosine Ib has been achieved in the presence of Candida antarctica and Pseudomonas sp. lipases in organic solvents starting from the 5'-acetyl derivative of 2'-deoxyinosine, an efficient chemoenzymatic synthesis of the antiviral drug 2',3'-dideoxyinosine has been achieved